2005
DOI: 10.1002/cphc.200400185
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap Widening of Titania through Semiconductor Support Interactions

Abstract: Silica-supported titania powders with 50, 36, 13 and 4 wt% of TiO2 (TiO2-50/SiO2, TiO2-36/SiO2, TiO2-13/SiO2 and TiO2-4/SiO2) were prepared by hydrolysis of TiCl4 in the presence of silica, followed by calcination at 500 degrees C. The formation of Ti-O-Si linkages was confirmed by diffuse reflectance infrared Fourier transform spectroscopy. Atomic force microscopy indicated the presence of titania crystals larger than 15 nm. All supported materials exhibited a blue-shift of the TiO2 absorption edge, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 28 publications
6
57
1
3
Order By: Relevance
“…The results are shown in Table 2. The value obtained for the TiO 2 P25 support is 3.0, close to that reported early [32,36] . Gold catalysts have lower band gap energies, a minimum values being detected for 0.24Au/Ti sample (Fig.…”
Section: Characterisationsupporting
confidence: 87%
See 1 more Smart Citation
“…The results are shown in Table 2. The value obtained for the TiO 2 P25 support is 3.0, close to that reported early [32,36] . Gold catalysts have lower band gap energies, a minimum values being detected for 0.24Au/Ti sample (Fig.…”
Section: Characterisationsupporting
confidence: 87%
“…5. The strong absorption observed at wavelengths lower than 400 nm is assigned to the intrinsic band gap absorption of TiO 2 [14,31,32]. The absorption edge shifts toward higher wavelengths for the gold catalysts, pointing out a decrease in the band gap energy of TiO 2 when supporting gold.…”
Section: Characterisationmentioning
confidence: 87%
“…In a recent study by Kisch and co-workers, the formation of covalent Ti-O-Si linkages in silica-supported TiO 2 powders was confirmed by FT-IR spectroscopy [128]. The supported materials exhibited a blue-shift of the TiO 2 absorption edge, which was attributed to an electronic semiconductor-support interaction mediated through surface Ti-O-Si bonds.…”
Section: Phase Interfaces In Tio 2 -Sio 2 Nanocompositesmentioning
confidence: 87%
“…The supported materials exhibited a blue-shift of the TiO 2 absorption edge, which was attributed to an electronic semiconductor-support interaction mediated through surface Ti-O-Si bonds. It was observed that the nanocomposite materials have lowered reducing power and, thus decreased driving force for oxygen reduction, due to the anodic shift of the conduction bands [128]. Furthermore, the researchers suggested that the charge recombination was accelerated in the silica-supported materials as compared to unsupported TiO 2 .…”
Section: Phase Interfaces In Tio 2 -Sio 2 Nanocompositesmentioning
confidence: 97%
See 1 more Smart Citation